Engagement of α3β1 and α2β1 integrins by hypervirulent Streptococcus agalactiae in invasion of polarized enterocytes - De Gaetano, Giuseppe Valerio; Lentini, Germana; Coppolino, Francesco; Famà, Agata; Pietrocola, Giampiero; Beninati, Concetta (Frontiers in Microbiology, 2024)
The gut represents an important site of colonization of the commensal bacterium Streptococcus agalactiae (group B Streptococcus or GBS), which can also behave as a deadly pathogen in neonates and adults. Invasion of the intestinal epithelial barrier is likely a crucial step in the pathogenesis of neonatal infections caused by GBS belonging to clonal complex 17 (CC17). We have previously shown that the prototypical CC17 BM110 strain invades polarized enterocyte-like cells through their lateral surfaces using an endocytic pathway. By analyzing the cellular distribution of putative GBS receptors in human enterocyte-like Caco-2 cells, we find here that the alpha 3 (α 3 ) and alpha 2 (α 2 ) integrin subunits are selectively expressed on lateral enterocyte surfaces at equatorial and parabasal levels along the vertical axis of polarized cells, in an area corresponding to GBS entry sites. The α 3 β 1 and α 2 β 1 integrins were not readily accessible in fully differentiated Caco-2 monolayers but could be exposed to specific antibodies after weakening of intercellular junctions in calcium-free media. Under these conditions, antiα 3 β 1 and anti-α 2 β 1 antibodies significantly reduced GBS adhesion to and invasion of enterocytes. After endocytosis, α 3 β 1 and α 2 β 1 integrins localized to areas of actin remodeling around GBS containing vacuoles. Taken together, these data indicate that GBS can invade enterocytes by binding to α 3 β 1 and α 2 β 1 integrins on the lateral membrane of polarized enterocytes, resulting in cytoskeletal remodeling and bacterial internalization. Blocking integrins might represent a viable strategy to prevent GBS invasion of gut epithelial tissues.